2016
DOI: 10.3847/0004-637x/830/2/100
|View full text |Cite
|
Sign up to set email alerts
|

The Chandra Cosmos-Legacy Survey: Source X-Ray Spectral Properties

Abstract: We present the X-ray spectral analysis of the 1855 extragalactic sources in the Chandra COSMOSLegacy survey catalog having more than 30 net counts in the 0.5-7 keV band. 38% of the sources are optically classified Type 1 active galactic nuclei (AGN), 60% are Type 2 AGN and 2% are passive, low-redshift galaxies. We study the distribution of AGN photon index Γ and of the intrinsic absorption N H,z based on the sources optical classification: Type 1 have a slightly steeper mean photon index Γ than Type 2 AGN, whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
201
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 140 publications
(208 citation statements)
references
References 96 publications
7
201
0
Order By: Relevance
“…These include unobscured AGN which have a N H < 10 22 cm −2 , obscured AGN which have a N H > 10 22 cm −2 and Compton thick AGN that have N H > 10 24 cm −2 . In the low-redshift (z < 1 − 2) universe, the AGN population is dominated by unobscured and obscured AGN, and the X-ray emission from these objects is best fit with a power-law index Γ ∼ 1.75 (e.g., Tozzi et al 2006;Marchesi et al 2016). …”
Section: Spectral Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…These include unobscured AGN which have a N H < 10 22 cm −2 , obscured AGN which have a N H > 10 22 cm −2 and Compton thick AGN that have N H > 10 24 cm −2 . In the low-redshift (z < 1 − 2) universe, the AGN population is dominated by unobscured and obscured AGN, and the X-ray emission from these objects is best fit with a power-law index Γ ∼ 1.75 (e.g., Tozzi et al 2006;Marchesi et al 2016). …”
Section: Spectral Propertiesmentioning
confidence: 99%
“…The hardness of the X-ray emission arising from an AGN over various redshifts have been studied extensively in a deep extragalactic X-ray survey using Chandra (e.g., Hickox et al 2009;Xue et al 2011;Marchesi et al 2016) and XMMNewton (e.g., Cappelluti et al 2009;Lanzuisi et al 2015). It has been shown that AGN with extended optical counterparts tend to exhibit harder X-ray emission due to the presence of significant gas absorbing softer photons, while AGN without a resolved counterpart tend to be softer (Hickox et al 2009).…”
Section: Spectral Hardness Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of possible contributions to our spectra from additional flux from sources located within the spectral extraction radii is performed using the source information provided by the COSMOS-Legacy catalog and the low-energy spectra extracted by Marchesi et al (2016). We did not try joint broadband models with the NuSTAR data (except for the CT source cosmos330) through complicated models, but rather used a flux estimate at low energy with a simple absorbed power-law model to evaluate possible contamination in common energy bands.…”
Section: Appendix Notes On Single Sourcesmentioning
confidence: 99%
“…In this framework, significant results have been obtained thanks to a number of high-sensitivityX-ray surveys with large and medium sky coverage,such as C-COSMOS Lanzuisi et al 2013), XMM-COSMOS ), COSMOS-Legacy Marchesi et al 2016), CDF-S Luo et al 2008;Xue et al 2011;Luo et al 2017), CDF-N (Brandt et al 2001;Alexander et al 2003;Xue et al 2016), Extended CDF-S (Lehmer et al 2005;Virani et al 2006;Xue et al 2016), AEGIS-X (Laird et al 2009), XMM-LSS (Pierre et al 2007(Pierre et al , 2016, and the XMM survey of CDF-S (Comastri et al 2011;Ranalli et al 2013). Among this set, the CDF-S survey, which recently reached a cumulative exposure time of 7Ms, represents the deepest observation of the X-ray sky obtained as of today and in the foreseeable future (Luo et al 2017).…”
Section: Introductionmentioning
confidence: 99%